Nanoscale Ti3O prepared from titanium metal powder, preparation method of nanoscale Ti3O and application of nanoscale Ti3O in preparation of acidic oxygen evolution electrocatalyst

Nanoscale Ti3O was synthesized by oxidizing nano-titanium metal powder, and a noble metal core-shell structured acidic oxygen evolution electrocatalyst was prepared, solving the problem of the difficulty in preparing Ti3O and realizing the preparation of highly efficient nanomaterials with excellent catalytic performance.

CN119551715APending Publication Date: 2025-03-04JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411745804.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare nanoscale Ti3O, and the preparation methods are demanding and difficult to scale up, which limits the application of Ti3O.

Method used

Nanoscale Ti3O was synthesized by calcining nano-titanium metal powder in a mixed atmosphere of oxygen and argon, and then used as a support to prepare a noble metal core-shell structured acidic oxygen evolution electrocatalyst.

Benefits of technology

The efficient preparation of nanoscale Ti3O was achieved, which has high conductivity and large specific surface area. The prepared acidic oxygen evolution electrocatalyst exhibits excellent catalytic activity and stability in acidic environments and is suitable for proton exchange membrane water electrolyzers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551715A_ABST
    Figure CN119551715A_ABST
Patent Text Reader

Abstract

The invention discloses nanoscale Ti3O prepared from titanium metal powder, a preparation method of the nanoscale Ti3O and application of the nanoscale Ti3O to preparation of an acidic oxygen evolution electrocatalyst, and belongs to the technical field of metal powder processing. According to the method, the nano titanium metal powder is used as a raw material and is controllably and selectively oxidized into the nano-scale Ti3O under the conditions of proper atmosphere, reaction temperature and reaction time, and the prepared nano-scale Ti3O has good conductivity and high specific surface area. The preparation method has the characteristics of simple process, low equipment and operation requirements, high product purity, high consistency and easiness in batch preparation, and the prepared nanoscale Ti3O can be used as a carrier of various noble metals, so that the acidic oxygen evolution electrocatalyst M (at) Ti3O with the noble metal core-shell structure is prepared, M is Pt, Ir, Rh or Ru, and the preparation method is simple and easy to implement. The prepared electrocatalyst has excellent acidic oxygen evolution reaction activity and stability, and has great application potential in a proton exchange membrane water electrolyser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder processing, and particularly relates to nano-scale Ti3O prepared from titanium metal powder, a preparation method and application of the nano-Ti3O in the preparation of an acidic oxygen evolution electrocatalyst. Background Art

[0002] Ti3O is a suboxide of titanium, and its unique structural feature is that oxygen is orderly distributed in the octahedral lattice gaps of titanium, occupying two-thirds of all octahedral gaps. Theoretical calculations and experimental results show that Ti3O has a high conductivity comparable to that of metallic titanium (npj Computational Materials, 2018, 4.1, 70), and therefore shows potential application prospects in the preparation of electrocatalysts. However, Ti3O is a metastable phase, which is extremely difficult to prepare and usually only appears as a by-product in titanium metal oxidation experiments under different atmospheres. Since TiO2 is a thermodynamically stable phase of titanium oxide, the titanium metal oxidation process is more likely to generate TiO2, while Ti3O faces competition with a variety of metastable phases of titanium oxides (such as TiO, Ti2O3, Ti3O5 and Ti4O7, etc.), which further increases the complexity of preparation.

[0003] At present, the reported Ti3O synthesis methods are extremely limited, and the conditions are extremely harsh. Early studies have been conducted by melting titanium and titanium dioxide by arc and sealing them in a vacuum glass tube for a week-long high-temperature reaction (Acta Chem. Scand 1957, 11.10, 1641-1652). This solid-solid reaction rate is extremely low, and vacuum conditions are difficult to achieve large-scale promotion. In addition, the Ti3O synthesized under such harsh reaction conditions is usually a bulk material with a larger size. In order to make Ti3O better applied, the nano-ization of materials is crucial. However, there is currently no feasible nano-Ti3O synthesis scheme, and the development of a simple and effective nano-synthesis method is a key research direction in the future. Summary of the invention

[0004] The present invention aims to provide a nano-scale Ti3O prepared from titanium metal powder, a preparation method and an application thereof in the preparation of an acidic oxygen evolution electrocatalyst.

[0005] The invention utilizes the controllable oxidation of nano titanium metal powder to synthesize nano-scale Ti3O with uniform particle size, and uses the nano-scale Ti3O as a carrier to prepare a series of noble metal core-shell acidic oxygen evolution electrocatalysts.

[0006] The first object of the present invention is to provide a method for preparing nano-sized Ti3O metal powder, the steps of which are as follows:

[0007] (1) loading nano titanium metal powder into a reaction container; wherein the particle size of the nano titanium metal powder is 30 to 300 nm, and the reaction container is an open container such as a corundum crucible or a porcelain boat;

[0008] (2) calcining the reaction vessel of step (1) in a mixed atmosphere of oxygen and argon at 600-650° C. for 2-5 h, and then cooling to room temperature to obtain the nano-sized TiO powder;

[0009] In the mixed atmosphere of oxygen and argon, the volume fraction of oxygen is 0.01% to 1%, and the rest is argon.

[0010] The second object of the present invention is to provide a nano-sized Ti3O, which is prepared by the above method.

[0011] The third object of the present invention is to provide an application of the above-mentioned nano-sized Ti3O in the preparation of an acidic oxygen evolution electrocatalyst, which uses nano-sized Ti3O as a carrier, disperses it in ethylene glycol, and then adds a precious metal source (chloroplatinic acid, chloroiridic acid, rhodium chloride or ruthenium trichloride, etc.), stirs the reaction at room temperature for 1 to 3 hours, and then reacts in an oil bath at 160 to 200°C for 3 to 5 hours; after the reaction is completed, it is cooled to room temperature, the reaction product is centrifuged and washed with water for multiple times, and after drying, an acidic oxygen evolution electrocatalyst M@Ti3O with a precious metal core-shell structure is obtained, where M=Pt, Ir, Rh or Ru, and the mass loading amount of the precious metal in the acidic oxygen evolution electrocatalyst is 20 to 40%.

[0012] Beneficial Effects

[0013] 1. The present invention can realize the preparation of nano-scale Ti3O powder, which has a particle size of about 100nm, a black-gray color, and a carbon dioxide content of 610S / cm 2 High conductivity and 77.3m 2 / g of large specific surface area; and the method of the present invention can quickly synthesize uniform powder under a controllable atmosphere, and has the characteristics of simple process, low equipment and operation requirements, high product purity, high consistency and easy batch preparation;

[0014] 2. Due to the small particle size and high uniformity of the synthesized Ti3O, a series of precious metal core-shell structured acidic oxygen evolution electrocatalysts prepared using it as a carrier have good dispersibility and are easy to disperse into highly uniform acidic oxygen evolution electrocatalyst slurry;

[0015] 3. The supported acidic oxygen evolution electrocatalyst Ir@Ti3O prepared by the present invention is an acidic oxygen evolution electrocatalyst with high acidic oxygen evolution reaction activity and stability. The iridium loading on the acidic oxygen evolution electrocatalyst electrode is 0.1 mg / cm 2 , the geometric current density reaches 10mA / cm 2The required overpotential is 279 mV, and it can operate stably for more than 300 h, which has great application potential in proton exchange membrane water electrolyzers. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 XRD spectrum of nano-Ti3O prepared in Example 1;

[0017] Figure 2 This is a SEM image of nano-sized Ti3O prepared in Example 1;

[0018] Figure 3 TEM image of nano-sized Ti3O prepared in Example 1;

[0019] Figure 4 This is a surface conductivity data diagram of nano-Ti3O prepared in Example 1;

[0020] Figure 5 This is a nitrogen adsorption-desorption curve of nano-sized Ti3O prepared in Example 1;

[0021] Figure 6 XRD spectrum of the Pt@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0022] Figure 7 TEM image of the Pt@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0023] Figure 8 XRD spectrum of Ir@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0024] Fig. 9 TEM image of the Ir@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0025] Fig.10 XRD spectrum of the Rh@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0026] Fig.11 TEM image of the Rh@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0027] Fig.12 XRD spectrum of Ru@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0028] Fig.13 TEM image of the Ru@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0029] Fig.14The linear voltammetric scanning curve of the Ir@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0030] Fig.15 The chronopotentiometry curve of the Ir@Ti3O acidic oxygen evolution electrocatalyst prepared in Example 1;

[0031] Fig.16 XRD spectrum (a) and SEM image (b) of nano-sized Ti3O prepared in Example 2;

[0032] Fig.17 XRD spectrum (a) and SEM image (b) of nano-sized Ti3O prepared in Example 3;

[0033] Fig.18 (a) XRD spectrum and (b) SEM image of nano-Ti3O prepared in Example 4. DETAILED DESCRIPTION

[0034] The present invention is further described in conjunction with the embodiments and drawings, but the protection scope of the present invention includes but is not limited to the following embodiments, and changes and adjustments made without departing from the spirit and scope of the present invention will also be included in the protection scope of the present invention.

[0035] The present invention is described below with reference to specific examples. The process condition values ​​in the following examples are exemplary, and the possible value ranges are as shown in the above invention content. For process parameters not specifically noted, conventional techniques can be used.

[0036] Example 1

[0037] Preparation of nano-scale Ti3O powder: 400 mg of nano-titanium metal powder with a particle size of 100 nm was placed in a corundum crucible and calcined at 600°C for 2 h (heating rate of 10°C / min) in a mixed atmosphere of oxygen and argon containing 0.01% oxygen by volume, and then naturally cooled to room temperature; the product was directly taken out from the crucible to obtain 440 mg of nano-scale Ti3O powder.

[0038] Preparation of noble metal core-shell structure acidic oxygen evolution electrocatalyst M@Ti3O (M = Pt, Ir, Rh, Ru): 100 mg of nano-Ti3O powder was ultrasonically dispersed in 40 mL of ethylene glycol, and the corresponding noble metal source (chloroplatinic acid, chloroiridic acid, rhodium chloride, ruthenium trichloride) was added according to the noble metal mass loading of 30 wt%; for example, when Ir@Ti3O is synthesized using chloroiridic acid as a raw material, the mass fraction of Ir is 30%, and the mass of Ir required is 43 mg, that is, 43 / 143 = 30%; the content of Ir in chloroiridic acid is 35%, so the mass amount of chloroiridic acid required is 43 / 35% =123 mg; similarly, the mass of chloroplatinic acid required for synthesizing Pt@Ti3O with a precious metal mass loading of 30 wt% is 90 mg, the mass of rhodium chloride required for synthesizing Rh@Ti3O with a precious metal mass loading of 30 wt% is 87 mg, and the mass of ruthenium trichloride required for synthesizing Ru@Ti3O with a precious metal mass loading of 30 wt% is 88 mg). After stirring at room temperature for 2 h, all the liquid was transferred to a round-bottom flask and reacted in an oil bath at 160 ° C for 3 h. After the reaction was completed, it was cooled to room temperature, the reaction product was centrifuged and washed with water several times, and finally dried to obtain 130 mg M@Ti3O (M=Pt, Ir, Rh, Ru) acidic oxygen evolution electrocatalyst.

[0039] Acidic oxygen evolution reaction performance test under three-electrode conditions: First, the acidic oxygen evolution electrocatalyst slurry was prepared. 4.7 mg Ti3O@Ir acidic oxygen evolution electrocatalyst was dispersed in 400 μL of naphthol dispersion (naphthol dispersion is an isopropanol solution with a naphthol volume fraction of 2.5%), and ultrasonicated in an ultrasonic machine for 1 h to obtain the acidic oxygen evolution electrocatalyst slurry; then 2 μL of the acidic oxygen evolution electrocatalyst slurry was transferred with a pipette and dropped on a platinum carbon electrode with an area of ​​0.071 / cm 2 , so the loading amount of precious metal iridium on the electrode is 0.1 mg / cm 2 .

[0040] The nano-Ti3O powder prepared by the above method and the Ir@Ti3O acidic oxygen evolution electrocatalyst prepared therefrom were characterized.

[0041] like Figure 1 As shown, the diffraction peak position of nano-sized Ti3O is consistent with the standard PDF card of Ti3O, proving that pure phase Ti3O was synthesized;

[0042] like Figure 2 and Figure 3 As shown, it can be observed that nanoscale Ti3O is composed of uniform particles of about 100 nm;

[0043] like Figure 4 As shown, the surface conductivity of nano-Ti3O reaches 610S / cm 2, proving its high electrical conductivity;

[0044] like Figure 5 As shown in Figure 2, the calculated specific surface area of ​​nano-Ti3O is 77.3 m 2 / g, proving that it is a high specific surface area material;

[0045] like Figure 6 As shown in the figure, the diffraction peak of nano-Ti3O is still maintained, and the diffraction peak of Pt single substance appears at the same time, which proves the successful loading of Pt particles;

[0046] like Figure 7 As shown, it can be observed that Pt nanoparticles are uniformly loaded on the nano-sized Ti3O to form a complete shell layer;

[0047] like Figure 8 As shown in the figure, the diffraction peak of nano-Ti3O is still maintained, and the diffraction peak of Ir single substance appears at the same time, which proves the successful loading of Ir particles;

[0048] like Fig. 9 As shown, it can be observed that Ir nanoparticles are uniformly loaded on the nano-sized Ti3O to form a complete shell layer;

[0049] like Fig.10 As shown, the diffraction peak of nano-Ti3O is still maintained, and the diffraction peak of Rh element appears at the same time, proving the successful loading of Rh particles;

[0050] like Fig.11 As shown, it can be observed that Rh nanoparticles are uniformly loaded on the nano-sized Ti3O to form a complete shell layer;

[0051] like Fig.12 As shown in the figure, the diffraction peak of nano-Ti3O is still maintained, and the diffraction peak of Ru element appears at the same time, which proves the successful loading of Ru particles.

[0052] like Fig.13 As shown, it can be observed that Ru nanoparticles are uniformly loaded on the nano-sized Ti3O to form a complete shell layer;

[0053] like Fig.14 As shown, the iridium loading on the electrode is 0.1 mg / cm 2 When the geometric current density of Ir@Ti3O reaches 10mA / cm 2 The overpotential required for the reaction is 279 mV, indicating that the acidic oxygen evolution electrocatalyst has excellent catalytic activity for oxygen evolution reaction.

[0054] like Fig.15 As shown, at 10mA / cm 2Ir@Ti3O can operate stably for more than 300 h at a current density of 1.34 W, indicating that the acidic oxygen evolution electrocatalyst has excellent catalytic stability for oxygen evolution reaction.

[0055] Example 2

[0056] This embodiment is the same as embodiment 1, except that the calcination temperature is changed to 650°C, and other synthesis conditions are not changed, and the same quality of nano-Ti3O powder can still be obtained. Fig.16 As shown in (a), the position of its diffraction peak is consistent with the standard PDF card of Ti3O, indicating that pure phase Ti3O was synthesized; Fig.16 As shown in (b), it can be observed that the sample is composed of uniform particles of about 100 nm. The XRD and SEM characterization results show that appropriately increasing the calcination temperature will not affect the preparation of nano-sized Ti3O.

[0057] Example 3

[0058] This embodiment is the same as the embodiment 1, except that the volume fraction of oxygen in the oxygen and argon atmospheres is changed to 1%, and other synthesis conditions are not changed, and the same quality of nano-Ti3O powder can still be obtained. Fig.17 As shown in (a), the position of its diffraction peak is consistent with the standard PDF card of Ti3O, indicating that pure phase Ti3O was synthesized; Fig.17 As shown in (b), it can be observed that the sample is composed of uniform particles of about 100 nm. The XRD and SEM characterization results show that appropriately increasing the oxygen content in the mixed atmosphere will not affect the preparation of nano-Ti3O.

[0059] Example 4

[0060] This embodiment is the same as embodiment 1, except that the calcination time is changed to 5h, and other synthesis conditions are not changed, and the same quality of nano-Ti3O powder can still be obtained. Fig.18 As shown in (a), the position of its diffraction peak is consistent with the standard PDF card of Ti3O, indicating that pure phase Ti3O was synthesized; Fig.18 As shown in (b), it can be observed that the sample is composed of uniform particles of about 100 nm; XRD and SEM characterization results show that appropriately extending the reaction time will not affect the preparation of nano-Ti3O.

Claims

1. A method for preparing nano-scale Ti3O from titanium metal powder, characterized in that: The steps are as follows: (1) placing nano titanium metal powder into a reaction vessel; (2) The reaction vessel of step (1) is calcined at 600-650° C. for 2-5 h in a mixed atmosphere of oxygen and argon, and then cooled to room temperature to obtain the nano-sized Ti3O powder.

2. A method for preparing nano-sized Ti3O from titanium metal powder as claimed in claim 1, characterized in that: In step (1), the particle size of the nano titanium metal powder is 30 to 300 nm, and the reaction container is an open container corundum crucible or a porcelain boat.

3. A method for preparing nano-sized Ti3O from titanium metal powder as claimed in claim 1, characterized in that: The heating rate during calcination in step (2) is 5 to 10°C / min.

4. A method for preparing nano-sized Ti3O from titanium metal powder as claimed in claim 1, characterized in that: In the mixed atmosphere of oxygen and argon in step (2), the volume fraction of oxygen is 0.01% to 1%, and the rest is argon.

5. A nano-scale Ti3O, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the nano-sized Ti3O as claimed in claim 5 in the preparation of an acidic oxygen evolution electrocatalyst.

7. The use of nano-sized Ti3O in the preparation of an acidic oxygen evolution electrocatalyst as claimed in claim 6, characterized in that: The method uses nano-sized Ti3O as a carrier, disperses it in ethylene glycol, adds a noble metal source, reacts for 1 to 3 hours at room temperature by stirring, and then reacts for 3 to 5 hours in an oil bath at 160 to 200°C. After the reaction is completed, the product is cooled to room temperature, centrifuged and washed with water for multiple times, and dried to obtain an acidic oxygen evolution electrocatalyst M@Ti3O with a noble metal core-shell structure, where M=Pt, Ir, Rh or Ru. The noble metal source is chloroplatinic acid, chloroiridic acid, rhodium chloride or ruthenium trichloride, and the mass loading amount of the noble metal in the acidic oxygen evolution electrocatalyst is 20 to 40%.